2022
DOI: 10.1039/d2dt01917e
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the electronic structure of MoO2/Mo2C/C by heterostructure and oxygen vacancies for boosting lithium storage kinetics

Abstract: The electronic structure regulation of the electrode materials can improve the ion/electron kinetics, which are beneficial to the cyclic performance and rate capability for lithium ion batteries (LIBs). Herein, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…66,69 The contributions of capacitance and diffusion to total charge storage could be further quantified using eqn (7), where i , k 1 v and k 2 v 1/2 were the total current, capacitance-controlled current and diffusion-controlled current, respectively. 50,67,68,70 The quantitative analysis results showed that the pseudo-capacitive contribution to the total charge for the f-V 2 C–MoS 2 @C electrode at 1 mV s −1 was 71%, while only 58% and 68% of the total charge storage came from the pseudo-capacitive behaviors of the f-V 2 C and MoS 2 @C electrode (Fig. 5e–g).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…66,69 The contributions of capacitance and diffusion to total charge storage could be further quantified using eqn (7), where i , k 1 v and k 2 v 1/2 were the total current, capacitance-controlled current and diffusion-controlled current, respectively. 50,67,68,70 The quantitative analysis results showed that the pseudo-capacitive contribution to the total charge for the f-V 2 C–MoS 2 @C electrode at 1 mV s −1 was 71%, while only 58% and 68% of the total charge storage came from the pseudo-capacitive behaviors of the f-V 2 C and MoS 2 @C electrode (Fig. 5e–g).…”
Section: Resultsmentioning
confidence: 98%
“…61,66,67 The b value could be determined by the slope of the log(i)-log(v) plot using eqn (6), and b = 0.5 and b = 0.1 implied that the diffusion-controlled process and surfacecontrolled pseudo-capacitive behaviors dominated the charge storage process, respectively. [63][64][65]68 The smaller movement in the position of the redox peaks with increasing scan rates (Fig. 5a-c) and the much higher b values (Fig.…”
Section: Lithium Storage Performancementioning
confidence: 96%